2018
DOI: 10.1038/s41591-018-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of placenta biology and genetic risk for schizophrenia

Abstract: Defining the environmental context in which genes enhance disease susceptibility can provide insight into the pathogenesis of complex disorders. We report that the intra-uterine environment modulates the association of schizophrenia with genomic risk (in this study, genome-wide association study-derived polygenic risk scores (PRSs)). In independent samples from the United States, Italy, and Germany, the liability of schizophrenia explained by PRS is more than five times greater in the presence of early-life co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
235
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(262 citation statements)
references
References 77 publications
24
235
2
1
Order By: Relevance
“…Accumulating evidences point to association of preeclampsia with brain developmental disorders, including intellectual disability, 15 epilepsy, 16 autism [17][18][19] and schizophrenia. 20,21 It might be partially due to the placenta-derived factors that affects the development of the brain and thus leads to complex brain disorders. 21,74 Ursini et al found that, for some loci of schizophrenia, the association between genetic risk and schizophrenia is affected by complicated pregnancies, and the gene set within these loci are differentially expressed in placentae from complicated in comparison with normal pregnancies 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating evidences point to association of preeclampsia with brain developmental disorders, including intellectual disability, 15 epilepsy, 16 autism [17][18][19] and schizophrenia. 20,21 It might be partially due to the placenta-derived factors that affects the development of the brain and thus leads to complex brain disorders. 21,74 Ursini et al found that, for some loci of schizophrenia, the association between genetic risk and schizophrenia is affected by complicated pregnancies, and the gene set within these loci are differentially expressed in placentae from complicated in comparison with normal pregnancies 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis reported that hypertensive disorders of pregnancy may be associated with an increase in the risk of ASD (autism spectrum disorder) and ADHD (attentiondeficit/hyperactivity disorder) 74 . Weinberger's study showed that the set of genes within genomic risk loci for schizophrenia that have interaction with intra-uterine and perinatal complications is highly expressed in placenta 21 . Other studies also demonstrated that preeclampsia was associated with increased risk of offspring schizophrenia.…”
Section: Schizophrenia Associated Genes Enriched In the Degs Of The Ementioning
confidence: 99%
See 2 more Smart Citations
“…It will also be important to not limit studies of potential mediators to IL‐6 and explore a range of other potential inflammatory mediators including but not limited to TNF‐α and IL‐17 (Choi et al, 2016; Jones et al, 2016). Moreover, given a recent study showing that most significant genetic variants associated with schizophrenia converge on a developmental trajectory sensitive to events that affect the placental response to in utero stressors, including pre‐eclampsia (Ursini et al, 2018), understanding the placental response in pre‐eclampsia and how this may predict or be associated with neurodevelopmental outcomes in pre‐eclampsia‐exposed offspring (O'Keeffe and Kenny, 2014), will be important questions for future research.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%